2021
DOI: 10.7554/elife.60999
|View full text |Cite
|
Sign up to set email alerts
|

Improved lipidomic profile mediates the effects of adherence to healthy lifestyles on coronary heart disease

Abstract: Adherence to healthy lifestyles is associated with reduced risk of coronary heart disease (CHD), but uncertainty persists about the underlying lipid pathway. In a case–control study of 4681 participants nested in the prospective China Kadoorie Biobank, 61 lipidomic markers in baseline plasma were measured by targeted nuclear magnetic resonance spectroscopy. Baseline lifestyles included smoking, alcohol consumption, dietary habit, physical activity, and adiposity levels. Genetic instrument was used to mimic the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
2
9
0
1
Order By: Relevance
“…Together with the other studies in clinical populations, the findings from this study, which was focused on individuals with elevated lipid levels without overt dyslipidemia, underscore the potential usefulness of lifestyle interventions, especially when delivered digitally, for both the primary and secondary prevention of cardiometabolic risk. In fact, effective digital lifestyle interventions appear to magnify the therapeutic benefit of cholesterol-lowering medication in those already past the clinical threshold and receiving medication, because of the complementary effects of the pharmacological and lifestyle interventions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together with the other studies in clinical populations, the findings from this study, which was focused on individuals with elevated lipid levels without overt dyslipidemia, underscore the potential usefulness of lifestyle interventions, especially when delivered digitally, for both the primary and secondary prevention of cardiometabolic risk. In fact, effective digital lifestyle interventions appear to magnify the therapeutic benefit of cholesterol-lowering medication in those already past the clinical threshold and receiving medication, because of the complementary effects of the pharmacological and lifestyle interventions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case-cohort study showed that drinking was inversely associated with non-fatal CHD risk, but positively associated with the risk of different stroke subtypes. A multivariable mendelian randomization study found that smoking was a risk factor for CVD even after adjusting for drinking [ 37 ]. Studies have shown that smoking is closely associated with the occurrence of carotid plaques, especially in current smokers [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case-cohort study showed that drinking was inversely associated with non-fatal CHD risk but positively associated with the risk of different stroke subtypes. A multivariable Mendelian randomization study found smoking was a risk factor for CVD even after adjusting for drinking [33][34] . Accordance with our results that lifestyle interventions, being no smoking and no drinking may greatly reduce the risk of carotid plaques in CHD.…”
Section: Discussionmentioning
confidence: 99%